English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1a)

x^2-2x-2=0

1b)

2x^2-8x+3=0

2a)

3x^2-4x-2=0

2c)

3x^2=2x+3

2006-10-22 09:53:59 · 2 answers · asked by koalabear 2 in Science & Mathematics Mathematics

2 answers

1a.)
x^2 - 2x - 2 = 0
x = (2 ± sqrt(4 - 4(1)(-2)))/(2(1))
x = 1 ± sqrt(3)


1b.)
2x^2 - 8x + 3 = 0
x = (8 ± sqrt(64 - 4(2)(3)))/(2(2))
x = (8 ± sqrt(64 - 24))/4
x = (8 ± 2sqrt(10))/4
x = (1/2)(4 ± sqrt(10))


2a.)
3x^2 -4x - 2 = 0
x = (4 ± sqrt(16 - 4(3)(-2)))/(2(3))
x = (4 ± sqrt(16 + 24))/6
x = (1/3)(2 ± sqrt(10))


2c.)
3x^2 = 2x + 3
3x^2 - 2x - 3 = 0
x = (2 ± sqrt(4 - 4(3)(-3)))/(2(3))
x = (2 ± sqrt(4 + 36))/6
x = (1/3)(1 ± sqrt(10))

2006-10-22 11:57:59 · answer #1 · answered by Anonymous · 0 0

Assuming you didn't mistype anything

1a.)
x^2 - 2x - 2 = 0
x = (2 ± sqrt(4 - 4(1)(-2)))/(2(1))
x = (2 ± sqrt(4 + 8))/2
x = (2 ± sqrt(12))/2
x = (2 ± 2sqrt(3))/2
x = 1 ± sqrt(3)

-----------------------------------------------

1b.)
2x^2 - 8x + 3 = 0
x = (8 ± sqrt(64 - 4(2)(3)))/(2(2))
x = (8 ± sqrt(64 - 24))/4
x = (8 ± sqrt(40))/4
x = (8 ± 2sqrt(10))/4
x = (1/2)(4 ± sqrt(10))

-------------------------------------------------

2a.)
3x^2 -4x - 2 = 0
x = (4 ± sqrt(16 - 4(3)(-2)))/(2(3))
x = (4 ± sqrt(16 + 24))/6
x = (4 ± sqrt(40))/6
x = (4 ± 2sqrt(10))/6
x = (1/3)(2 ± sqrt(10))

-------------------------------------------

2c.)
3x^2 = 2x + 3
3x^2 - 2x - 3 = 0
x = (2 ± sqrt(4 - 4(3)(-3)))/(2(3))
x = (2 ± sqrt(4 + 36))/6
x = (2 ± sqrt(40))/6
x = (2 ± 2sqrt(10))/6
x = (1/3)(1 ± sqrt(10))

2006-10-22 17:07:32 · answer #2 · answered by Sherman81 6 · 0 1

fedest.com, questions and answers